Strategi Mapping Classroom dengan model Quantum Teaching Untuk Meningkatkan Percaya Diri Tampil di depan Publik Untuk Generasi Kota Batam - Andriyansah, Andriyansah; Hendrayanaama, Angga Sucitra; Thaibd, Dina; Sylvana, Andi; Maesaroh, Imas; Nasoha, Mohamad (Abdimas Indonesian Journal, 2024)
The urgency of this activity is to increase the courage of the younger generation to appear with good communication in front of the public. The purpose of this activity is to train the younger generation who are students to be able to communicate. The problem that occurs is the lack of confidence to appear in front of the public, the benefit of this activity is that the training participants are expected to be able to appear in front of the public individually or in groups. The target of this activity is that participants display artistic creativity uploaded on social media, namely tiktok. generation to run the wheels of Indonesia EMAS for that it is necessary to carry out activities that can improve their abilities. There were 350 participants, the training technique used the Mapping Classroom Strategy approach so that participants could communicate in small groups as the first step. Then the material is given using the Quantum Teaching model which involves speakers and participants to explore talents that can be presented and staged in publications on social media.